CONQUERING CUSTOMER HEARTS : INTELLIGENT HYPER-PERSONALIZATION WITH ARTIFICIAL INTELLIGENCE FOR ENHANCED CUSTOMER ENGAGEMENT - Tjioe, Gabrielle; Wijaya, Brigitta Maggie; Evarianto, Jason Frederick; Darmawan, Vincent Adelwin; Erwin, Erwin (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Indonesia is undergoing a rapid digital transformation, characterized by the integration of artificial intelligence (AI) across diverse sectors. AI possesses the potential to reshape consumer behavior and unlock novel opportunities for businesses, including the educational sector, to cultivate more personalized relationships with customers through hyper-personalization. This study aims to analyze the impact of Artificial Intelligence and Hyper-Personalization on customer engagement levels, with the aspiration of contributing to the development of more effective marketing strategies in the digital age. The primary focus of this research is to investigate how personalized marketing strategies, leveraging artificial intelligence, can influence customer interaction and loyalty towards offered products and services. This research employs a quantitative approach, utilizing a sample of 246 respondents possessing knowledge of digital marketing. Data were collected via an online questionnaire distributed through Google Forms and subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS version 8 software. The research instrument utilized a 5-point Likert scale. The findings of this study reveal that both Artificial Intelligence (AI) and Hyper-Personalization exert a positive and significant influence on Customer Engagement. Furthermore, AI demonstrates a positive and significant impact on Hyper-Personalization. Hyper-Personalization mediates the relationship between AI and Customer Engagement, although a reduction in significance was observed due to a mismatch between Hyper-Personalization and the heterogeneous content characteristics of social media platforms targeting diverse audiences. This research provides insights into how the implementation of AI in marketing can foster stronger relationships between businesses and customers. While AI can enhance customer engagement through personalization, the utilization of more generalized content, acceptable to a broad audience, proves more effective, particularly for social media content within educational institutions.